Oncogenic Signaling Pathways in Mucopolysaccharidoses - Silva, Gerda Cristal Villalba; Soares, Luis Dias Ferreira; Matte, Ursula (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Cancer cells depend on several signaling pathways and organelles, such as the lysosomes. Defects in the activity of lysosomal hydrolases involved in glycosaminoglycan degradation lead to a group of lysosomal storage diseases called Mucopolysaccharidoses (MPS). In MPS, secondary cell disturbance affects pathways common to cancer. This work aims to identify oncogenic pathways related to cancer in the different MPS datasets available in public databases and compare the ontologies across the different types of MPS. For this, we used 12 expression datasets of 6 types of MPS. Statistical analysis was based on hypergeometric distribution followed by FDR correction. We found several enriched pathways across the 12 MPS studies, among being 57.65% were KEGG pathways, 32.5% of GO Biological Process, 2.5% GO Celular Component, and 7.35% GO Molecular Function. Hippo signaling pathway and MAPK signaling pathway appear in all datasets. Proteoglycans in cancer, Rap1 signaling pathway, and Cytokinemediated signaling pathway appears in 11 of 12 datasets. The lysosome participates in several biological processes, like autophagy, cell adhesion and migration, and antigen presentation. These processes also may affect in several types of cancer and Lysosomal Storage Diseases. Studying the tumor ontology signature in lysosomal disorders may help understand lysosomal storage diseases and cancer’s underlying mechanisms. This may help amplify therapeutic approaches for both types of diseases.